An examination of stock split and special dividend announcements in relation to market-timing opportunities, business cycles, and monthly patterns : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Finance at Massey University, School of Economics and Finance, College of Business, Massey University - Hu, May (Massey University, 2012)
This dissertation investigates the explanations for the aggregate corporate activities of stock split and special dividend announcements in the United States (US) listed firms between 1926 and 2008. The study is motivated by the limitation of understanding of these two types of events, which have previously only been focused at the firm-specific level. Further, by studying stock splits and special dividends, this research seeks to find an answer to the debate regarding explanations of corporate event waves between neoclassical efficiency reasons and modern market-timing hypothesis. The study is also motivated by the lack of a link between the extensively documented January Effect and Halloween Effect in stock markets and corporate practice. In addition to the contribution of the extended dataset provided in this research, the study has examined corporate decisions to announce stock splits and special dividends from a macro-perspective, especially in relation to market-timing opportunities, economic efficiency reasons, and calendar monthly effects. Chapter 1 is the introduction of this dissertation. Chapter 2 provides a comprehensive critical literature review on this topic. Chapter 3 is the research framework, hypothesis development, data and methodology used in this research. Chapter 4 is the initial results of the patterns and frequencies for stock split and special dividend announcements. Chapter 5 first investigates whether market conditions and investor sentiment affect the aggregate activities of stock splits and special dividends. These findings indicate that firms time the market to split shares during bull markets with positive and increasing sentiment to achieve higher abnormal returns. On the other hand, special dividend distributions are more likely to happen in bear markets when sentiment decreases. Firms paying special dividends in bear markets are better performers than their counterparts in bull markets. Chapter 6 then examines whether stock split and special dividend activities are driven by the business cycle. Stock splits are more likely to happen in the economic growth stage rather than in the mature stage. On the contrary, firms tend to distribute extra cash dividends to alleviate agency problems in economic declines when profitable investment opportunities are low. Chapter 7 explores the relationship between the patterns of stock splits and special dividend announcements and the calendar anomalies of the January Effect and the Halloween Effect. Firms are more likely to split shares in January and Halloween period than in other months of a year. However, firms have a commonality to pay special dividends to their shareholders in November and December. Lastly, Chapter 8 assesses which macro-determinant has the strongest explanatorypower on stock splits and special dividend activities, and the results show that the businesscycle effect is the quantitatively strongest along with all the additional and robustness checks. Chapter 9 is the conclusion and remarks of this dissertation, including future research ideas in the related areas.
Keywords: Stock splitting; Dividends; Business cycles; Stock splits; Announcements; United States